Performance and emission analysis of rubber seed, palm, and their combined blend in a multi-cylinder diesel engine - Adam, I.K. (MDPI AG, 2018)
In consideration of its vast resources in Malaysia, the potential use of a nonedible biodiesel source from rubber seed oil (RSO) is explored. However, a mixture with a high saturation content feedstock is required to increase its oxidation stability, which is caused by its 78.93 unsaturation content. Two blends of 20 and 50 v/v rubber seed biodiesel (RB) or palm biodiesel (PB) and varying percentage mixtures of these two feedstock oils biodiesel (RPB) were evaluated on combustion performance in a 55 kW multi-cylinder diesel engine at full load conditions. The results showed that feedstock blending offered benefits in terms of fuel properties enhancement, improved engine performance, and reduced emissions. In comparison to RB, RPB showed higher brake power (BP) of 1.18-2.97 and lower brake specific fuel consumption (BSFC) of 0.85-3.69, smoke opacity (11.89-14.19), carbon monoxide (CO) of 2.48-6.93, hydrocarbon (HC) of 2.36-9.34, and Nitrogen oxide (NO) emissions of 2.34-5.93. The cylinder pressures and heat release rates (HRR) of RPB blends were 8.47-11.43 and 36.02-46.61 higher than diesel, respectively. The start of combustion angles (SOC) of RB and RPB blends were from â13 to â15â¦C and from â13.2 to â15.6 crank angle degree (â¦CA) before top dead center (BTDC), but the combustion delays were 6-8â¦C and 5.4-7.8â¦C shorter when compared to diesel fuel which were â10â¦C BTDC and 11â¦C, respectively. It can be concluded that RPB blends showed better performance and emissions over the individual rubber seed and palm biodiesel blends and can replace diesel fuel in unmodified engines. Â© 2018 by the authors. Licensee MDPI, Basel, Switzerland.